The Effect of Social Appearance Anxiety on Psychological Well-Being: A Study on Women Doing Regular Pilates Activities - Mehdi Duyan, Mehmet Ilkim, Talip Çelik, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to investigate the effect of social appearance anxiety on womens’ psychological well-being. Methods: In this study, a relational screening model was used as one of the quantitative research methods. The study group was selected by convenience sampling method, which is one of the non-random sampling methods. The universe of this research consists of women who do pilates, while the sample consists of a total of 382 women who participated in the pilates exercise program in Istanbul, Izmir, Muğla, Hatay and Malatya provinces of Turkey. Participants with less than 1 year of sports experience were not included in this study. The study was based on voluntary participation. As data collection tools, social appearance anxiety and psychological well-being scale were used. A questionnaire was applied to the pilates participants participating in the research through electronic communication tools. Data obtained from participants were analyzed using SPSS and Amos 20.0. In the research, descriptive statistics, correlation, confirmatory factor analysis, and hierarchical regression analysis were performed. Results: According to the research findings, it was determined that there is a significant and negative relationship between social appearance anxiety and psychological well-being (r = -.250; p < 0.01). In addition, it has been found that social appearance anxiety has a significant and negative effect on psychological well-being (β= -.253; p<0.001). Conclusion: As a result of this study, it was determined that Pilates exercises reduce social appearance anxiety and increase psychological well-being. It can be said that when women who do regular pilates exercises develop a positive physical image, they are more at peace with themselves and increase their psychological well-being.